Pénzügyi képességek és a mélyszegény, szegregált roma családok pénzügyi helyzete - Kosztopulosz Andreász (KÖZGAZDASÁGI SZEMLE, 2024)
Financial inclusion is often seen by policy makers as a tool for social inclusion, while financial literacy is seen as an important tool to support financial inclusion. Along this logic, financial inclusion and the well-being of spatially segregated, stigmatised and extremely poor groups of society can be supported through the development of financial literacy. In our study, we explore the validity of this chain of logic, building on a long-term collaborative process, based on semi-structured in-depth individual interviews and qualitative observations. Our conclusion is that the above chain of logic (financial literacy → financial inclusion → well-being) reflects a middle-class perspective and as such is rather provincial, as there are a number of subsistence strategies in the communities concerned that cannot be measured and interpreted by conventional approaches to financial literacy. Thus, in order to effectively promote the social inclusion of those concerned, one should focus on the specific social conversion factors, as emphasised by the concept of financial capability, related to segregation, poverty and stigmatisation.